(untitled) (TEST Ticontre. Theory Text Translation, 2022)
This article aims at analyzing the presence of the myth of Don Juan within the pages of Honoré de Blazac’s La Comédie humaine. As a sort of modern myth par excellence, the story of Don Juan takes different forms throughout Balzac’s work: for example, it is taken as a model for some of the major figures of seducers depicted in the Comédie, and in Le Cabinet des Antiques as well as in Les Secrets de la Princesse de Cadignan we might even recognize a female version of Don Juan in the character of Diane de Maufrigneuse. At the same time, however, Don Juan also becomes a key figure that epitomizes Balzac’s philosophical thought as presented in L’Elixir de longue vie, a “conte fantastique” published in 1830.